2012
DOI: 10.1097/ccm.0b013e3182653269
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the use of an insulin infusion for the management of hyperglycemia in critically ill patients

Abstract: While the benefits of tight glycemic control have not been definitive, there are patients who will receive insulin infusion therapy, and the suggestions in this article provide the structure for safe and effective use of this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
423
3
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(450 citation statements)
references
References 214 publications
(277 reference statements)
9
423
3
15
Order By: Relevance
“…Important processes of care for insulin therapy include use of a validated insulin titration program, frequent BG monitoring, and avoidance of finger‐stick glucose testing through the use of arterial or venous glucose samples 35. Furnary et al 36.…”
Section: Insulin Therapy In Patients With Perioperative Hyperglycemiamentioning
confidence: 99%
“…Important processes of care for insulin therapy include use of a validated insulin titration program, frequent BG monitoring, and avoidance of finger‐stick glucose testing through the use of arterial or venous glucose samples 35. Furnary et al 36.…”
Section: Insulin Therapy In Patients With Perioperative Hyperglycemiamentioning
confidence: 99%
“…[30,37] Subcutaneous and intravenous insulins are valid options for managing hyperglycemia. The use of intravenous infusion of insulin is reserved for critical patients where exist the possibility for a tighter control, [30,38] and patients with marked hyperglycemia because is achieves better control. [4,39] For more stable patients and patients in non-ICU, the insulin can be administered by mixing it in nutritional parenteral bag safely.…”
Section: Journal Of Translational Internal Medicine / Oct-dec 2016 / mentioning
confidence: 99%
“…240 More recently, the emphasis has shifted from diabetes to hyperglycaemia, where new-onset hyperglycaemia (compared with hyperglycaemia in known diabetics) may hold a much higher risk of adverse outcome. 240,241 Studies in the field of critical care have demonstrated the detrimental effect of hyperglycaemia, due to an adverse effect on renal and hepatic function, endothelial function, and immune response, particularly in patients without underlying diabetes. Oxidative stress (a major cause of macrovascular disease) is triggered by swings in blood glucose, more than by sustained and persistent hyperglycaemia.…”
Section: Disturbed Glucose Metabolismmentioning
confidence: 99%
“…Minimization of the degree of glucose variability may be cardioprotective, and mortality may correlate more closely with blood glucose variability than mean blood glucose per se. 240,241 A significant number of surgical patients will have previously undiagnosed pre-diabetes, and are at increased risk of unrecognised perioperative hyperglycaemia and the attendant adverse outcomes. Although there is no evidence that screening low-or moderate-risk adults for diabetes improves outcomes, it may reduce complications in high-risk adults.…”
Section: Disturbed Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation